Aptamers with Tunable Affinity Enable Single‐Molecule Tracking and Localization of Membrane Receptors on Living Cancer Cells. (28th August 2020) - Delcanale, Pietro; Porciani, David; Pujals, Silvia; Jurkevich, Alexander; Chetrusca, Andrian; Tawiah, Kwaku D.; Burke, Donald H.; Albertazzi, Lorenzo
Abstract: Tumor cell‐surface markers are usually overexpressed or mutated protein receptors for which spatiotemporal regulation differs between and within cancers. Single‐molecule fluorescence imaging can profile individual markers in different cellular contexts with molecular precision. However, standard single‐molecule imaging methods based on overexpressed genetically encoded tags or cumbersome probes can significantly alter the native state of receptors. We introduce a live‐cell points accumulation for imaging in nanoscale topography (PAINT) method that exploits aptamers as minimally invasive affinity probes. Localization and tracking of individual receptors are based on stochastic and transient binding between aptamers and their targets. We demonstrated single‐molecule imaging of a model tumor marker (EGFR) on a panel of living cancer cells. Affinity to EGFR was finely tuned by rational engineering of aptamer sequences to define receptor motion and/or native receptor density. Abstract : Localization and tracking of individual membrane receptors on living cells was achieved upon transient binding of aptamer probes through minimally invasive solution diffusion. Probe affinity was modulated by rational engineering of the aptamer sequence. Detection of single molecules is linked to binding affinity, so probes with different affinity provide readouts on different properties, such as diffusive dynamics and receptor density levels.